MODEL FOR LOCATION DEVELOPMENT OF ATM BANKING SERVICE IN URBAN AREA - Rini Rachmawati; Nur Mohammad Farda; R. Rijanta; Sara Dwi Kumiarto (Faculty of Geography, Universitas Gadjah Mada, 2009)
The research aims to (iesign a determination modelfor the locations of ICTbased economic service particularly the ATM (Automatic Teller Machine) service.The initial step of this research was to compile a database of the ATM service useby respondents in JjJekasiCity. The data base covered the locations of the ATMsthe respondents visited and their reasons for choosing those locations. The nextstep was to perform the network and spatial analysis by using Arc View GIS 3.x todetermine the optimal service locations. The research result shows that: 1) Thelocations of ATM placement were mostly found in areas of trade and service,industry and regular residence, 2) The orientation of ATM location developmentrequired by the people was on regular and irregular residence considering theshort distance, 3) In determining optimal ATM locations attention must be paid tothe parameter of distance between the location and trade and service areas as wellas the regular residence. The use of network analysis is indeed helpful indeveloping model of the service location in the determination of optimal servicearea.